Differential Expression Profiles and Functional Prediction of tRNA-Derived Small RNAs in Rats After Traumatic Spinal Cord Injury - Qin, Chuan; Feng, Hao; Zhang, Chao; Zhang, Xin; Liu, Yi; Yang, De-Gang; Du, Liang-Jie; Sun, Ying-Chun; Yang, Ming-Liang; Gao, Feng; Li, Jian-Jun (Frontiers in Molecular Neuroscience, 2020)
Spinal cord injury (SCI) is mostly caused by trauma. As the primary mechanical injury is unavoidable, a focus on the underlying molecular mechanisms of the SCI-induced secondary injury is necessary to develop promising treatments for patients with SCI. Transfer RNA-derived small RNA (tsRNA) is a novel class of short, non-coding RNA, possessing potential regulatory functions in various diseases. However, the functional roles of tsRNAs in traumatic SCI have not been determined yet. We used a combination of sequencing, quantitative reverse transcription-polymerase chain reaction (qRT-PCR), bioinformatics, and luciferase reporter assay to screen the expression profiles and identify the functional roles of tsRNAs after SCI. As a result, 297 differentially expressed tsRNAs were identified in rats’ spinal cord 1 day after contusion. Of those, 155 tsRNAs were significantly differentially expressed: 91 were significantly up-regulated, whereas 64 were significantly down-regulated after SCI (fold change > 1.5; P < 0.05). Bioinformatics analyses revealed candidate tsRNAs (tiRNA-Gly-GCC-001, tRF-Gly-GCC-012, tRF-Gly-GCC-013, and tRF-Gly-GCC-016) that might play regulatory roles through the mitogen-activated protein kinase (MAPK) and neurotrophin signaling pathways by targeting brain-derived neurotrophic factor (BDNF). We validated the candidate tsRNAs and found opposite trends in the expression levels of the tsRNAs and BDNF after SCI. Finally, tiRNA-Gly-GCC-001 was identified to target BDNF using the luciferase reporter assay. In summary, we found an altered tsRNA expression pattern and predicted tiRNA-Gly-GCC-001 might be involved in the MAPK and neurotrophin pathways by targeting the BDNF, thus regulating the post-SCI pathophysiologic processes. This study provides novel insights for future investigations to explore the mechanisms and therapeutic targets for SCI.